STRATEGI BRANDING AIR TERJUN TUMPAK SEWU LUMAJANG DALAM UPAYA MENARIK PENGUNJUNG - Rahmau’dina, Revina Widya; Ekoputro, Widiyatmo (Sintesa, 2025)
ABSTRAK Tumpak Sewu Waterfall, located on the slopes of Mount Semeru in Lumajang Regency, East Java, is one of the leading tourist destinations with extraordinary visual appeal and natural uniqueness. However, the overall brandingused has not been optimal in attracting a wide range of visitors. This study aims to analyze brandingstrategies that can be applied using Keller's (1993) Destination Brandingtheory with a Customer-Based Brand Equity (CBBE) approach and the Destination Brand Equity dimensions proposed by Konecnik and Gartner (2007). This approach examines elements such as brand awareness, brand associations, perceived quality, and visitor loyalty toward the destination. These elements are also interconnected with the implementation of quality branding, service, and recognition. The research method used is a descriptive qualitative approach, employing data collection techniques such as interviews with informants, field observations, and documentation. The research results indicate that the brandingstrategies employed include strengthening visual identity, collaborating with tourism travel agents, optimizing digital media, and involving local communities in management as POKDARWIS, which can build strong destination brand equity and impact increased tourist visits and local economic empowerment. Keywords: Destination Branding, Tumpak Sewu Waterfall, Brand Equity, Tourism Strategy